Integrated effect of inorganic and organic nitrogen sources on nutrient uptake and crop quality of broccoli - Hussain, Md. Jamal; AJM Sirajul Karim; ARM Solaiman; Md. Shafiqul Islam; Rahman, Mizanur (Agriculture and Natural Resources, 2021)
The integrated effect was investigated of inorganic and organic nitrogen sources on nutrient uptake and crop quality of broccoli at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh. The experiment was designed based on 24 treatment combinations (integrated plant nutrition system [IPNS]-based) with four doses of inorganic nitrogen sources at 140, 160 and 180 kg N/ha as urea super granules (USG) and 180 kg N/ha as prilled urea (PU) in combination with two levels of three organic nitrogen sources being 1) 1 t/ha and 2 t/ha mustard oil cake (OC); 2) 2 t/ha and 3 t/ha poultry manure (PM) and 3) 3 t/ha and 5 t/ha cow dung (CD). The results indicated that the single-photon avalanche diode (SPAD) value, nutrient uptake, nitrogen use efficiency and the head quality (compactness co-efficient, vitamin C, β-carotene and chlorophyll content) of broccoli were superior following USG-organic manure integration compared to PU-organic manure. Integration of USG-organic manure increased the head compactness with the highest compactness coefficient (21.92) from USG-N160×OC2. Almost all the parameters such as nutrient (N, P, K, S) uptake and head quality had increased values with increasing rates of inorganic and organic fertilizer; however, N use efficiency and vitamin C contents were slightly decreased with increasing levels of inorganic and organic fertilizer. Maximum N uptake (208.33 kg/ha) was produced with USG-N180×OC2 followed by USG-N160×OC2 (204.30 kg/ha), but the maximum N use efficiency (92.89%) was obtained with USG-N140×OC2 followed by USG-N160×OC2 (89.06%). The highest vitamin C of 87.28 mg/100 g fresh weight (FW) and β-carotene content of 0.393 mg/100 g FW were produced with both USG-N160×PM3 and USG-N180×PM3.